Information Flow Identification using the Package Marking System - Narasimha Murty, D. Saravanan KVSSN (Journal of Informatics Education and Research, 2023)
With the development of Internet technology and its applications, a large number of important services provided by the network, and therefore become increasingly important for security and network availability. Circulated Repudiation of Facility attack has one very complex in nature difficult to solve this kind of attack that has security issues, disaster prevention and detection are easy to make and hard for other reasons. This website does great harm to normal operation. Due to the TCP / IP protocol itself to take advantage of the shortcomings of Circulated Repudiation of Facility attackers to send packages with invalid source IP addresses are allowed. As a result, you can achieve the purpose of the attack is hidden. This is when they are using the wrong IP source addresses to quickly and accurately locate the attackers emerged as a key issue. In this situation, the source address of the corresponding detector technology is a research hotspot.Researchers environments such as connection testing, ICMP Trace back, marking the package, and the source package overlay networks, monitor the various proposed solutions Currently, the majority of the address of the explorer at home and abroad. These solutions, with their own strengths and effective solution to the above problem weaknesses. This paper focuses to resolve the above mentioned issues effectively, and the experiments result also verified that.